Gastric glomus tumor with uncertain malignant potential: case report of a rare cause of upper gastrointestinal bleeding - Fejes, Roland; Gyorgyev, Kitti Szonja; Góg, Csaba; Krenács, László; Zombori, Tamás; Széll, Zsófia Eszter; Balajthy, Zsófia; Pancsa, Tamás; Simonka, Zsolt (World journal of surgical oncology, 2024)
BACKGROUND: Glomus tumors (GTs) are mesenchymal neoplasms that are typically benign. Gastric GTs are uncommon and occur mainly in the upper gastrointestinal tract. Malignant gastric GTs are extremely rare, constituting less than 1% of gastric tumors. Because their features are similar to those of other tumors found in the same gastrointestinal region, such as stromal tumors, leiomyomas, lymphomas, and lipomas, the diagnosis is challenging. CASE PRESENTATION: A 52-year-old male patient presented with fatigue and melena. The initial endoscopic examination did not locate any source of bleeding. Six months later, pan-gastroscopy, performed due to progressive microcytic anemia, revealed a 40 × 30 mm polypoid lesion with deep ulcerations; histopathological analysis confirmed that it was a gastric GT with expression of alpha-actin and cadherin 17 and a Ki-67 index of 20%. The patient delayed surgical therapy until his symptoms worsened. Laparoscopic sleeve resection revealed a 65 × 45 × 25 mm tumor, and secondary immunohistochemical analysis revealed extensive spread into the mucosa and subserosa. Focally, the tumor bulged into some large veins. Genetic examination with RNA isolation further supported the histopathological diagnosis of gastric GT with uncertain malignant potential. CONCLUSIONS: This case underscores the diagnostic challenges posed by gastric GTs because they are rare and their clinical features are similar to those of other gastric tumors. Thorough histopathological and molecular analysis is essential for an accurate diagnosis. Surgical intervention remains the primary therapeutic approach. This case also emphasizes the need for long-term follow-up due to the potential for recurrence and malignancy.
Keywords: Stomach Neoplasms; Gastroscopy; Prognosis; Middle Aged; mužské pohlaví; Stomach; Gastrointestinal Hemorrhage; gastrointestinální krvácení; prognóza; gastroskopie; Humans; Gastrointestinal malignancy; lidé středního věku; Upper gastrointestinal bleeding; Glomus tumor; glomangiom; Glomus Tumor; lidé; Male; nádory žaludku